2020
DOI: 10.3389/fneur.2020.00154
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Lipid Infiltration Is Associated With Cerebral Aneurysm Rupture

Abstract: Background: Intracranial aneurysm wall degradation can be associated with lipid infiltration. However, the relationship between lipid infiltration and aneurysm rupture has not been explored quantitatively. To investigate the correlation between lipid infiltration and aneurysm rupture, we utilized patient-specific simulation of low-density lipoprotein (LDL) transport to analyze lipid infiltration in the cerebral aneurysm wall. Methods: Sixty-two aneurysms were analyzed. Patient blood pressure, plasma LDL concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…These functions of HDL-C may explain why HDL-C reduces the risk of IA rupture. The pathological study indicated that an increase in lipid infiltration is associated with IA rupture [15,42], and Frösen and Ollikainen et al were the first to elucidate in depth the accumulation of LDL and HDL particles in the aneurysm wall [15,43]. Combined with our research, we speculate that this may be due to the passive repair of IA by lipids.…”
Section: F I G U R Esupporting
confidence: 78%
“…These functions of HDL-C may explain why HDL-C reduces the risk of IA rupture. The pathological study indicated that an increase in lipid infiltration is associated with IA rupture [15,42], and Frösen and Ollikainen et al were the first to elucidate in depth the accumulation of LDL and HDL particles in the aneurysm wall [15,43]. Combined with our research, we speculate that this may be due to the passive repair of IA by lipids.…”
Section: F I G U R Esupporting
confidence: 78%
“…Hyperlipidemia and lipid accumulation have been suggested to be related to aneurysm rupture (18,(31)(32)(33). Triglyceride is commonly recognized as a risk factor for cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…The repeated microbleeds from these new fragile vasa vasorum further promote inflammatory cell accumulation ( 28 ). Acute and chronic inflammatory cell accumulations accelerate aneurysm enlargement and induce aneurysm rupture ( 29 ).…”
Section: Discussionmentioning
confidence: 99%